SOCIAL IMPACT OF NARCOTICS ABUSE IN INDONESIA - Musyawir Halim, Muhammad; Ujung, Amiruddin; Mubarak Lubis, Syahrin; Riziq Ashari, Muhammad; Prasatya, Dimas (Proceeding International Seminar of Islamic Studies, 2023)
Drug abuse has a negative impact on humans. Drug abusers tend to experience personality disorders, including anxiety, emotional, depression and impaired mental health. This condition also has an impact on the social aspects of association and acceptance of the surrounding community and the economic aspects of the cost of purchasing illegal drugs, health restoration and other social costs. The problem in this research is: How is the impact of drug abuse on social and economic aspects in DKI Jakarta Province?”. The research method used is qualitative with a case study approach. The data collection method is through informants, namely practitioners within the DKI Jakarta Provincial National Narcotics Agency (BNNP) and former drug addicts/abusers as well as various other related documents. The purpose of this study was to describe the impact of drug abuse on social and economic aspects in the Province of DKI Jakarta so that it can be dealt with effectively. The results showed that the condition of drug abuse in DKI Jakarta tends to be low but the increase is stable. Drug abusers have a negative impact on social and economic aspects. To overcome this, an effective strategy is needed through prevention, community empowerment, eradication and rehabilitation. This research is recommended to the BNNP DKI to innovate more effective drug abuse strategies and to members of the public to live healthy and productive lives without drugs.